2013
DOI: 10.1371/journal.pone.0084525
|View full text |Cite
|
Sign up to set email alerts
|

Two-Exon Skipping within MLPH Is Associated with Coat Color Dilution in Rabbits

Abstract: Coat color dilution turns black coat color to blue and red color to cream and is a characteristic in many mammalian species. Matings among Netherland Dwarf, Loh, and Lionhead Dwarf rabbits over two generations gave evidence for a monogenic autosomal recessive inheritance of coat colour dilution. Histological analyses showed non-uniformly distributed, large, agglomerating melanin granules in the hair bulbs of coat color diluted rabbits. We sequenced the cDNA of MLPH in two dilute and one black rabbit for polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…In the present study, we sequenced 1689 bp of the entire CDS region of the Rex rabbit MLPH gene, and 13 SNPs were found in 15 exons. Lehner et al (2013) found that, in both colour diluted rabbits (Netherland Dwarf and Loh), the skipping of exons 3 and 4 was present. This resulted in altered amino acids at p.QGL (Reed, 1989;Krawczak et al, 1992;Roscigno et al, 1993) QWA and a premature stop codon at p.K40*.…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, we sequenced 1689 bp of the entire CDS region of the Rex rabbit MLPH gene, and 13 SNPs were found in 15 exons. Lehner et al (2013) found that, in both colour diluted rabbits (Netherland Dwarf and Loh), the skipping of exons 3 and 4 was present. This resulted in altered amino acids at p.QGL (Reed, 1989;Krawczak et al, 1992;Roscigno et al, 1993) QWA and a premature stop codon at p.K40*.…”
Section: Discussionmentioning
confidence: 93%
“…A number of genes have been found in this study with different splices involved in hair color dilution. A strongly truncated protein caused by an MLPH splice variant leads to a form of hair color dilution in rabbits [35]. The deletion of SLC7A11 in the region from the 11th intron to the adjacent Pcdh18 gene, which changes the amino acid sequence, reduces the formation of melanin, and thus affects coat color [36].…”
Section: Discussionmentioning
confidence: 99%
“…The MLPH gene codes for melanophilin. The MLPH gene polymorphism is associated with the "diluted" phenotype of many animal species, including cats (Ishida et al, 2006), dogs (Philipp et al, 2005), and rabbits (Lehner et al, 2013). The MATP gene encodes for the Membrane Associated Transporter Protein (MATP), also known as the solute carrier family 45 member 2 (SLC45A2).…”
Section: High-throughput Genetic Techniquesnext-generation Sequencingmentioning
confidence: 99%